Poverty Eradication in North-Western Nigeria: An Evaluation of Social Investment Programs - Abubakar Sunday, Ayuba; Muhammad, Alhaji Ibrahim; Ibrahim, Shu'aibu; Mohd Afifi, Bahurudin Setambah (INTI International University, 2023)
Poverty in Nigeria is palpable and evident even in the presence of rich material and human resources. The federal government of Nigeria has introduced many intervention programmes like the social investment programme. The social investment program federal government of Nigeria was established in 2016 with the main objective of tackling poverty and hunger across the country. The program was designed to ensure a more equitable distribution of resources to vulnerable populations, including children, youth and women. The government has four programs: N-Power for young graduates to develop skills, Conditional Cash Transfer for those in extreme poverty, Government Enterprise and Empowerment Program for traders, and School Feeding Program to increase school enrollment. To date, the government have been investing a large amount of their annual budget into the program. The objective of this study was to evaluate the effectiveness of the Nigerian federal government's social investment program. The study focused on the program's objectives, its approach to addressing the needs of poverty-stricken individuals, and its strengths and weaknesses. The study adopted a qualitative research design. The participants were twenty (20) persons drawn from five northwestern states of Nigeria. Data were generated using a structured interview. The collected data was analyzed and categorized into themes. The findings showed that the programme aims to reduce poverty by creating jobs for the youth and helping people set up businesses. However, finding revealed that the objectives of the government programme were not met as the trainees could not be employed. The programme needs wider coverage, strict supervision, and monitoring to achieve its goals. The weaknesses of the programme include politics, corruption, bribery and lack of transparency. It was recommended that the government and stakeholders should decentralize the programme and honest and transparent people should be incorporated.